2015
DOI: 10.1186/s12991-014-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and tolerability of quetiapine in patients with schizophrenia who switched from other antipsychotics because of inadequate therapeutic response—a prospective open-label study

Abstract: BackgroundWhile the frequency and importance of antipsychotic switching in patients with schizophrenia, there is insufficient evidence with regard to switching strategy. Quetiapine is one of the drugs of choice for switch because of its unique receptor profile. However, there were no data on the long-term clinical and neurocognitive effect of quetiapine in patients who had responded inadequately to prior antipsychotics. The purpose of this study is to examine the long-term efficacy and tolerability of quetiapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…A study by Roussidis and colleagues showed that switching a patient’s antipsychotic medication for reasons related to lack of efficacy and/or tolerability was associated with a significantly improved clinical benefit and increased adherence to treatment [ 74 ]. Similarly, studies of patients switching to olanzapine [ 28 ], quetiapine [ 29 , 34 ], ziprasidone [ 33 , 75 ], aripiprazole [ 76 ], long-acting injectable risperidone [ 32 , 77 ], or paliperidone [ 36 ] have reported improvements in cognitive function, psychotic symptoms, and/or tolerability during up to one year of treatment. However, the current analysis is the only switch study to examine long-term changes in subjective responses, tolerability, adherence-related attitude, and HRQoL using the disease-specific PETiT assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Roussidis and colleagues showed that switching a patient’s antipsychotic medication for reasons related to lack of efficacy and/or tolerability was associated with a significantly improved clinical benefit and increased adherence to treatment [ 74 ]. Similarly, studies of patients switching to olanzapine [ 28 ], quetiapine [ 29 , 34 ], ziprasidone [ 33 , 75 ], aripiprazole [ 76 ], long-acting injectable risperidone [ 32 , 77 ], or paliperidone [ 36 ] have reported improvements in cognitive function, psychotic symptoms, and/or tolerability during up to one year of treatment. However, the current analysis is the only switch study to examine long-term changes in subjective responses, tolerability, adherence-related attitude, and HRQoL using the disease-specific PETiT assessment.…”
Section: Discussionmentioning
confidence: 99%
“…There are cognitive dysfunctions also present in depression, which have been shown to persist even when the affective symptoms are in remission, and worsen with every depressive episode [2,4,5]. This implies two things: one, the cognitive and affective aspects of depression are independent of each other, and two, the neural underpinnings of depression might persist even if affective symptoms aren’t displayed.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of depression-related cognition have focused, therefore, on spatial processes, because they are hippocampal-dependent [3640]. However, spatial memory deficits do not fully encompass the cognitive dysfunction seen in depressed patients [2,3,5,29]. Novel object recognition (NOR has been shown to rely on structures distinct from the hippocampus, and is considered a cognitive, not spatial task [4144].…”
Section: Introductionmentioning
confidence: 99%
“…This patient had been ingesting stones probably over a long period and showed a rare presentation of acute intestinal obstruction. While such a clinical presentation has been reported in the literature, 23 25 none of the patients, to our best knowledge, had ingested such a large amount of stones so as to cover the length of the large bowel (from the colon to the rectum). The findings of hematological indices and iron studies suggestive of IDA were consistent with most of the case reports on pica.…”
Section: Discussionmentioning
confidence: 76%